2000
DOI: 10.1614/0043-1745(2000)048[0007:ioeban]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ethylene biosynthesis and necrosis in weed leaves by aFusarium oxysporumprotein

Abstract: A small assortment of microbial proteins have the ability to activate defense responses and induce necrosis in plant cells through cell signaling pathways. These proteins are of interest because of their potential use as bioherbicides and inducers of plant resistance in agriculture. A 24-kDa protein (Nep1) was purified from culture filtrates of Fusarium oxysporum, and the effects of this protein on weed leaves were investigated. This protein induced necrosis in detached leaves of Papaver somniferum, Lycopersic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 31 publications
1
31
0
1
Order By: Relevance
“…Studies in Maryland showed that L. draba did not develop visible leaf necrosis after exposure to a microbial protein (Nep1) purified from Fusarium oxysporum Schltndl: Fr., but did respond with ethylene biosynthesis at high Nep1 concentration levels (Jennings et al 2000). The comparatively low responses of L. draba suggest that the use of Nep1 as a biologically based alternative to herbicides would be less effective than for many other weeds in the study.…”
Section: Response To Other Human Manipulationmentioning
confidence: 74%
“…Studies in Maryland showed that L. draba did not develop visible leaf necrosis after exposure to a microbial protein (Nep1) purified from Fusarium oxysporum Schltndl: Fr., but did respond with ethylene biosynthesis at high Nep1 concentration levels (Jennings et al 2000). The comparatively low responses of L. draba suggest that the use of Nep1 as a biologically based alternative to herbicides would be less effective than for many other weeds in the study.…”
Section: Response To Other Human Manipulationmentioning
confidence: 74%
“…It has been demonstrated that Nep1 causes extensive foliar necrosis when applied as a foliar spray to dicot weed species [15,16], an activity that has not been demonstrated for other necrosis inducing proteins whether toxins or elicitors. Critical to the response of plants to foliar sprays with Nep1 is the inclusion of surfactants (Silwet-L77) which appears to allow penetration of the leaf epidermal layer through stomata [15,16].…”
Section: Cell Culture Experimentsmentioning
confidence: 97%
“…Critical to the response of plants to foliar sprays with Nep1 is the inclusion of surfactants (Silwet-L77) which appears to allow penetration of the leaf epidermal layer through stomata [15,16]. Nep1 promotes disease in at least one plantpathogen interaction [17] and is compatible with some herbicides [16].…”
Section: Cell Culture Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[15][16][17][18][19][20] Biotic stress (e.g., pathogen attack) elicits ethylene synthesis in plants. 21 Ethylene production by Fusarium spp in vitro was measured under comparable conditions.…”
Section: Introductionmentioning
confidence: 99%